Ask Question
23 August, 03:17

Multiply the polynomials (x+1) (4x^2+7x+6)

+3
Answers (1)
  1. 23 August, 05:14
    0
    The final form would be 4x^3 + 11x^2 + 13x + 6

    Step-by-step explanation:

    In order to get the value of these polynomials when multiplied, start by multiplying the x by each term in the second parenthesis.

    x * 4x^2 = 4x^3

    x * 7x = 7x^2

    x * 6 = 6x

    Now we also need to multiply each by 1.

    1 * 4x^2 = 4x^2

    1 * 7x = 7x

    1 * 6 = 6

    Now we add all the terms together and combine like terms.

    4x^3 + 7x^2 + 6x + 4x^2 + 7x + 6

    4x^3 + 11x^2 + 13x + 6
Know the Answer?